Renegotiating problematic relationships: An art-based sculpting method to address reactivity across disciplines. (1st July 2022) - Govoni, Devon; Teoli, Laura; Summer, Dan
This article details an art-based sculpting method designed to assist professionals in exploring reactivity and difficulties within therapeutic relationships. The authors describe the Four-Phase Sculpting Method (FPSM), research specific to the method and how it was adapted for use in clinical practice, education, training and professional development. The FPSM addresses challenging relationships through the creation of a three-dimensional sculpture in four distinct phases: a creation phase, breakdown phase, mending phase and renegotiation phase. During these phases, emotions are given a form and explored through a continual process of dialoguing and witnessing. Research outcomes indicate that the method promotes transformation of thoughts and feelings, resulting in a greater understanding of the self and others. The authors discuss the FPSM and how they incorporated it into a variety of academic and professional settings over the past several years. Furthermore, the authors provide an overview of interdisciplinary applications of the FPSM.